The Development of Tarutung Into a City - Pertiwih Siahaan; Budi Agustono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This article discusses the history of the formation of the city of Tarutung. This article answers the problem of how the city of Tarutung developed after the arrival of Western colonialism in the form of religion, military, administration and economy which encouraged the development of Tarutung City. This study uses the historical method through four stages: heuristics (collection of historical sources); verification (source criticism); interpretation (historical analysis and interpretation); and historiography (writing history). Sources as historical data obtained from a number of documents and literature from the colonial to post-colonial period. This study found that the existing Tarutung city was formed into a traditional city which was used as a trading center from a durian tree that grew in the middle of the village with the Batak Toba socio-culture that was implemented before the arrival of Western colonialism. The arrival and colonial influence made the identity of Tarutung City begin to develop both in terms of social, economic, and cultural aspects while maintaining the traditional cultural elements that still exist.